Exploring the Experiences of Family Caregivers Caring for Patient with Tuberculosis at Home - Tambunan, Evelyn Hemme (Jurnal Ners, 2023)
The family has a very important role in the recovery of family members who suffer from Tuberculosis. This study aims to explore the experiences of family caregivers caring for family members who are suffering from Tuberculosis at home. This research is a qualitative study, where exploratory and descriptive in nature and phenomenology was followed. A semi-structured interview with open ended questions was answered by 16 participants, who are caring family members suffering from Tuberculosis. The data was analyzed using Interpretive Phenomenology Analysis that was approved by Komite Etik Penelitian Fakultas Ilmu Keperawatan Universitas Advent Indonesia. The data analysis resulted in the extraction of three themes including family role in Tuberculosis care and support, family caregivers behavior in transmission of disease and family caregivers knowledge of disease.Various experiences described by family caregivers in caring family members suffering from Tuberculosis. The future research needed to provide sustainable education to enhance family knowledge related to Tuberculosis care at home.